THE IMPACT OF USING MIND MAPPING TECHNIQUES ON STUDENTS’ PROFICIENCY IN COMPREHENDING ANALYTICAL EXPOSITION AT 11th GRADE STUDENTS OF SMAN 1 HINAI - Nurhafna Pasaribu; Sondang Manik; Sahlan Tampubolon (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2026)
This study aimed to determine the impact of using mind mapping techniques on students’ proficiency in comprehending analytical exposition texts at the eleventh grade students of SMAN 1 Hinai. The study applied Classroom Action Research involving two cycles consisting of planning, action, observation, and reflection. The participants were students of class XI IPA-1. The data were collected through observation, interviews, questionnaires, photographs, pre-test, and post-tests. The findings showed that the implementation of mind mapping significantly improved students’ reading comprehension. The mean score increased from 57.99 in the pre-test to 68.29 in post-test 1 and reached 80.31 in post-test 2. Besides improving students’ achievement, mind mapping also created a more active, motivated, and positive classroom atmosphere. Students became more enthusiastic in participating during the learning process and showed better understanding in identifying main ideas, implicit and explicit information, references, and word meanings in analytical exposition texts.